Laboratory evaluation of the potential masking of color changes produced by silver diamine fluoride in primary molars - Dina Hamdy; Maria Giraki; Amr Abd Elaziz; Amira Badran; Gehan Allam; Stefan Ruettermann (BMC, 2021)
Abstract Background The importance of Silver diamine fluoride (SDF) as a minimally invasive and nonaerosolizing management during COVID-19 pandemic has highly increased. SDF is a caries-arresting agent that causes staining of tooth structure. Managing this discoloration will increase its acceptance in treating primary teeth. The main aim of this study was to quantify the color change associated with the application of SDF on extracted carious primary molars, the potential masking of this color change by potassium iodide (KI), composite (CMP) and glass ionomer cement (GI) and the effect of aging on this color masking effect. Methods An in-vitro study in which 52 carious primary molars were collected, prepared, and distributed randomly into four groups equally as follows: Group A: SDF 38%; Group B: SDF 38% + KI; Group C: SDF 38% + CMP; Group D: SDF 38% + GI. Color changes were recorded for each sample at baseline, and after application of the tested materials. Moreover, all samples had undergone Suntest aging followed by a third color reading. CIELAB values L*, a*, b*, ΔL, Δa, and Δb were measured, ΔE was calculated, and data were analyzed using multivariate analysis of variance (MANOVA) and post-Hoc Scheffé test (p < 0.05). Results MANOVA revealed the significant influence of the factor 'material'. SDF caused an obvious color change compared to the color of carious dentin. Regarding ΔL, the color change of groups C and D was not significant directly after application of the tested materials. After aging, it was significant among all groups, including groups C and D. In Δa there was a difference between SDF and groups B and C after application of the tested materials, and aging produced the same results. The color shifts of Δb of all tested groups varied significantly from one another. After aging, there was no difference between group D and either group A or B. Conclusions Treatment with SDF caused obvious discoloration of carious dentin. Directly after SDF application, all tested materials could effectively mask the color change associated with the application of SDF. CMP was the only material whose color masking effect was not completely reversed by aging.